Validez del cuestionario cardiovascular MONICA comparado con la historia clínica Validity of the MONICA cardiovascular questionnaire compared with clinical records - José M. Baena-Díez; María T. Alzamora-Sas; María Grau; Isaac Subirana; Joan Vila; Pere Torán; Ylenia García-Navarro; Noemí Bermúdez-Chillida; Judit Alegre-Basagaña; María Viozquez-Meia; Jaume Marrugat (Elsevier, 2009)
Objetivo: Estudiar la validez del cuestionario cardiovascular Multinational Monitoring of Trends and Determinants in Cardiovascular Disease (MONICA) comparado con la historia clínica. Métodos: Estudio descriptivo, prospectivo, multicéntrico, realizado en 3.329 personas >50 años de edad (estudio ARTPER [arteriografía periférica]). La muestra se seleccionó por muestreo aleatorio simple en 32 centros de salud de atención primaria. Los diagnósticos considerados fueron: infarto agudo de miocardio, ángor, enfermedad vascular cerebral, hipertensión arterial, diabetes mellitus e hipercolesterolemia. Se estudió además el tratamiento con antihipertensivos, hipolipemiantes o insulina, hipoglucemiantes y antiagregantes o anticoagulantes. La validez entre cuestionario y registro en la historia clínica se estudió con la sensibilidad, la especificidad, los valores predictivos y el índice kappa. Resultados: La edad media fue de 65 años (desviación estándar: 8,9), y el 54,8% eran mujeres. La sensibilidad del cuestionario fue >90% en todas las variables, excepto en el ángor (89,9%) y la enfermedad vascular cerebral (86,5%). La especificidad también fue >90%, excepto en el ángor (88,3%) y la hipercolesterolemia (77,5%). El valor predictivo positivo fue >90% en todos los tratamientos farmacológicos; >80% en el ángor, el infarto agudo de miocardio y la hipertensión arterial; 79,4% en la enfermedad vascular cerebral; 79,1% en la hipercolesterolemia, y 73,4% en la diabetes mellitus. Los valores predictivos negativos fueron >90% en todos los casos. Los índices kappa fueron >0,80 en todas las variables, excepto en la hipercolesterolemia (0,69) y la diabetes mellitus (0,79). Conclusiones: El cuestionario cardiovascular MONICA es un método válido para encuestar a las personas >50 años sobre sus enfermedades, factores de riesgo y tratamientos cardiovasculares. Objective: To assess the validity of the questionnaire Multinational Monitoring of Trends and Determinants in Cardiovascular Disease (MONICA) compared with clinical records. Methods: A descriptive, prospective, multicenter study was performed within the framework of the Peripheral Arterial Disease Study (PERART) in 3,329 persons aged >50 years old. The sample was selected by simple random sampling in 32 primary health care centers. The diagnoses included were acute myocardial infarction, angina pectoris, cerebrovascular disease, hypertension, diabetes mellitus, and hypercholesterolemia. Treatment variables were also considered (antihypertensive, lipid-lowering and hypoglycemic agents or insulin, as well as antiplatelet or anticoagulant agents). The sensitivity, specificity, predictive values, and kappa index were computed to test the validity of the MONICA questionnaire. Results: The mean age was 65 years (SD 8.9) and 54.8% were women. The sensitivity of the questionnaire was >90% for all the variables apart from angina pectoris (89.9%) and cerebrovascular disease (86.5%). Specificity was also >90%, except for angina pectoris (88.3%) and hypercholesterolemia (77.5%). The positive predictive value was >90% for all the treatments; >80% for angina pectoris, acute myocardial infarction and hypertension; 79.4% for cerebrovascular disease; 79.1% for hypercholesterolemia and 73.4% for diabetes mellitus. The negative predictive value was >90% for all the variables. The kappa indexes were >0.80 for all the variables apart from hypercholesterolemia (0.69) and diabetes mellitus (0.79). Conclusions: The MONICA cardiovascular questionnaire is valid in the assessment of cardiovascular disease, risk factors and treatments in patients aged >50 years old.